Islamic Legal Ethics in Faith-Based Addiction Recovery: A Socio-Legal Model of Behavioral Transformation - Ahmad Saefulloh; Tobroni; Zainap Hartati; Kadar Risman; Riza Awal Novanto; Zakia Zuzanti; Saprun; Moncef Ben Abdeljelil (El-Mashlahah, 2026)
The study examines how Islamic legal ethics has functioned as an organizing logic in addiction recovery within a faith-based rehabilitation context. Conventional approaches to drug rehabilitation often emphasize biomedical and behavioral interventions while overlooking the ethical and spiritual dimensions that shape individuals’ lived experiences of recovery. Therefore, the particular study aimed to address this gap by analyzing recovery as a socio-legal and moral transformation process. The study employed an empirical legal research design with a qualitative approach grounded in transcendental phenomenology. Data were collected through in-depth interviews, participant observation, and document analysis at a faith-based rehabilitation institution in Indonesia, involving six recovering participants and one key informant with diverse recovery experiences. The findings reveal that recovery is experienced as a gradual transformation from emotional detachment and externally driven behavior toward internalized ethical awareness. Spiritual practices, such as prayer and zikr, play a crucial role in fostering ethical discipline and self-control, which in turn, support behavioral transformation and sustained recovery outcomes. Detoxification is understood not as a purely biomedical intervention but as part of a structured ethical and spiritual system. Then, the particular study contributes by positioning Islamic legal ethics as a central framework in addiction recovery and offering a socio-legal model that integrates spirituality, ethical discipline, and behavioral change. The findings suggest that rehabilitation programs should incorporate ethical reflection and spiritual engagement to enhance long-term recovery sustainability.